Koordinasi Publik untuk Pengurangan Risiko Bencana (PRB) Banjir pada Pelaksanaan Pembangunan Berkelanjutan Gorontalo - Ivan Taslim; Muh. Firyal Akbar (Department of Urban and Regional Planning, Diponegoro University, 2019)
In flood-prone areas, coordination between parties in disaster risk reduction (DRR) activities is very important. This is because the consequences of disasters will directly affect the disruption of people's lives and livelihoods, and also hinder the process of sustainable development. The study aims to develop a public coordinating scheme for disaster risk reduction (DRR) activities based on public resources in Gorontalo Regency. Public resources from government agencies and society are available in Gorontalo Regency with their respective tasks at the stages before, during and after the disaster. Public coordination is expected to support the implementation of DRR-based sustainable development in Gorontalo Regency. The preparation of public coordination scheme begins with geospatial flood hazard assessment based on the characteristics of the Limboto Watershed using a Geographic Information System (GIS) tool. The result provides a basis for the implementation of public coordination arrangements for DRR. Gorontalo Regency is dominated by a coastal land parcel adjacent to Tomini Bay, stretching from lowland plains to hilly mountains. High rainfall, critical land use and settlements in the lowlands have caused the study area categorized into high- to very high-risk zones of flooding. To ensure sustainable development runs effectively, its implementation must be based on DRR policy with public coordination. Public coordination is carried out between government agencies and society, who cooperate in compliance with their respective roles and tasks at the stage before, during and after the disaster. The results show that the involvement of more sectoral parties is needed at the stage before and during the disaster. This indicates that public coordination before the disaster performs risk prevention and reduction activity that should be prioritized in the implementation of development before inhibiting its sustainability.